Trade Openness and Economic Growth in West Africa: A Case Study of WAEMU and WAMZ Blocs - (:unkn) unknown (My University, 2022)
This study investigated the effect of trade openness on economic growth in West Africa from 1990 to 2021. To achieve this objective, West Africa was partitioned into two economic blocs of West African Economic Monetary Union (WAEMU) and West African Monetary Zone (WAMZ) due to central monetary authority heterogeneity, currency harmonization, monetary policy differences and language differentials. We collected data on the variables used from the United Nations Conference on Trade and Development (UNCTAD) and World Development Indicator (WDI) of the World Bank. The model for the study was cast in dynamic form and analysed using the Pooled Mean Group (PMG) method. In West Africa, total trade and imports demand catalyzed economic growth, as exports demand slowed down output expansion. We observed differential effect of trade openness on economic growth across the WAEMU and WAMZ. Total trade and exports demand slowed the pace of output growth in the WAEMU countries, while imports openness insignificantly enhanced economic growth in the bloc. In the WAMZ bloc, better output performance is achieved through increased exports openness as our result suggested that total trade and imports openness were insignificant in affecting output level in the WAMZ bloc. On the strength of this, we recommend that West African countries design and implement export-promotion policies that could transition their economies from producers of primary products to manufactured commodities. This will ensure their economies are resilient to external shocks.
Keywords: African Research